Religion and international migration - Kaya, Ayhan (Edward Elgar Publishing Ltd., 2021)
This chapter is an attempt to contribute to analysis of the complex relationship between religion and international migration. As it is impossible to cover the whole issue of religion and international migration in one chapter, this chapter is selective in the sense that only a few dimensions will be discussed in order to shed light on this intricate relationship. The chapter is composed of four subsections: reification of religion in migrancy; religious roots of the discourse of hospitality vi-a-vis refugees; and the sources of Islamic radicalisation and the politics of honour in migration among Muslims residing in Europe. The chapter’s background, mainly based on secondary literature, also lies in the findings of my empirical research that I have been conducting since the late 1990s in European countries among Muslim-origin residents as well as the native populations. The chapter commences with a summary of the relevant literature in Migration Studies, Diaspora Studies and Theology to address the relationship between religion and international migration. The current state of the art will be followed by the depiction of the ways in which religion is reified in migrants’ everyday life. Afterwards, there will be a discussion on the religious roots of the politics of hospitality that has been a common practice in Europe and beyond, at least temporarily, vis-à-vis refugees and asylum seekers originating from Syria, Afghanistan, Iraq, Iran, Eritrea, Senegal and elsewhere. The last section of the chapter is also based on another current debate, which is Islamic radicalisation and the revival of honour among diasporic Muslim communities. © The Editor and Contributors Severally 2021.